Generalization of exposure in vivo in Complex Regional Pain Syndrome type I - Hollander, Marlies den; de Jong, Jeroen; Onghena, Patrick; Vlaeyen, Johan W.S. (Behaviour research and therapy, 2020)
Exposure in vivo has been found successful in reducing pain-related fear, disability, and experienced pain in chronic pain patients. Despite the success of exposure treatment, experimental studies show that extinction learning is fragile, raising doubts whether extinction of pain-related fear generalizes to new threatening activities after treatment. This study examined whether a particular exposure treatment, in which patients are exposed to a variety of activities (Multiple Exposure condition), promotes generalization of extinction to new threatening situations, compared to an exposure treatment in which subjects are repeatedly exposed to the same set of activities (Repeated Exposure condition). Generalization tests were combined with randomized replicated single case experimental designs (N = 8). Included were patients with Complex Regional Pain Syndrome type I reporting elevated levels of pain-related fear. The Multiple Exposure treatment condition consisted of at least 15 activities to which patients were exposed once. The Repeated Exposure treatment condition exposed patients to only three activities during five sessions each. Generalization was tested by exposing patients to new fearful activities post-treatment and 6-months follow-up. Patients from both conditions performed equally well at both generalization tests. Daily measures showed that the Multiple Exposure condition is preferred to reduce fear of movement/(re)injury, pain catastrophizing and pain experience. •Will Multiple Exposure or Repeated Exposure promote generalization of clinical exposure treatment in pain-related fear?•Generalization tests were combined with randomized replicated single case experimental designs (N=8).•Patients with Complex Regional Pain Syndrome type I and high levels of pain-related fear participated in the study.•All patients performed several new threatening activities at generalization tests post-treatment and 6 months follow-up.•Regardless of condition, significant changes occurred in the performance of personally relevant activities.•Multiple Exposure is preferred over Repeated Exposure to change fear of movement, pain-catastrophizing and pain-experience.